Comparison of optimal performance at 300 keV of three direct electron detectors for use in low dose electron microscopy - McMullan, G. (Elsevier, 2014)
Low dose electron imaging applications such as electron cryo-microscopy are now benefitting from the improved performance and flexibility of recently introduced electron imaging detectors in which electrons are directly incident on backthinned CMOS sensors. There are currently three commercially available detectors of this type: the Direct Electron DE-20, the FEI Falcon II and the Gatan K2 Summit. These have different characteristics and so it is important to compare their imaging properties carefully with a view to optimise how each is used. Results at 300 keV for both the modulation transfer function (MTF) and the detective quantum efficiency (DQE) are presented. Of these, the DQE is the most important in the study of radiation sensitive samples where detector performance is crucial. We find that all three detectors have a better DQE than film. The K2 Summit has the best DQE at low spatial frequencies but with increasing spatial frequency its DQE falls below that of the Falcon II.